2017
DOI: 10.1097/pts.0000000000000436
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Patients' Perceptions of Safety Culture in the Hospital Setting: Development and Initial Evaluation of the Patients' Perceptions of Safety Culture Scale

Abstract: The Patients' Perceptions of Safety Culture scale contributes to both a more comprehensive view of patients' experience of healthcare and a more balanced approach to safety culture measurement in healthcare. It contributes to an increased recognition of patients' views on safety-relevant aspects of their care that provide important inputs to patient safety improvement.This is an open-access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives License 4.0 (CCBY-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…43 Distinct from other self-report surveys, the Patients' Perceptions of Safety Culture scale was designed to assess patient, rather than staff, perceptions of hospital safety culture. 44 Qualitative and mixed methods studies assessing safety culture The review identified 31 studies (4.5%) that used qualitative or mixed methods to assess safety culture. Interviews were the most common approach (n=23; 74.2%), followed by frameworks and theories (n=11, 35.5%), and focus groups (n=9, 29%) (see table 3).…”
Section: Resultsmentioning
confidence: 99%
“…43 Distinct from other self-report surveys, the Patients' Perceptions of Safety Culture scale was designed to assess patient, rather than staff, perceptions of hospital safety culture. 44 Qualitative and mixed methods studies assessing safety culture The review identified 31 studies (4.5%) that used qualitative or mixed methods to assess safety culture. Interviews were the most common approach (n=23; 74.2%), followed by frameworks and theories (n=11, 35.5%), and focus groups (n=9, 29%) (see table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Future research may wish to verify and evaluate the theoretical PSC construct using the HSOPS-NS in samples from other hospitals and other cultures, or among patients (Monaca et al, 2017). Future studies may also wish to use the instrument to analyze the construct's relationship with incident rates or results in the field of patient safety.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Only with the new century has a safety culture permeated into the values and norms of health care organization members [ 12 , 13 , 14 ]. Now, patient safety has become an important element of care quality, first evaluated by experts and health professionals and ultimately including patients’ feedback about their care [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%